Characterization of a Newly Discovered Symbiont of the Whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) - Bing, Xiao-Li (American Society for Microbiology, 2013)
Bemisia tabaci (Hemiptera: Aleyrodidae) is a species complex containing >28 cryptic species, some of which are important crop pests worldwide. Like many other sap-sucking insects, whiteflies harbor an obligatory symbiont, “Candidatus Portiera aleyrodidarum,” and a number of secondary symbionts. So far, six genera of secondary symbionts have been identified in B. tabaci. In this study, we report and describe the finding of an additional bacterium in the indigenous B. tabaci cryptic species China 1 (formerly known as B. tabaci biotype ZHJ3). Phylogenetic analysis based on the 16S rRNA and gltA genes showed that the bacterium belongs to the Alphaproteobacteria subdivision of the Proteobacteria and has a close relationship with human pathogens of the genus Orientia. Consequently, we temporarily named it Orientia-like organism (OLO). OLO was found in six of eight wild populations of B. tabaci China 1, with the infection rate ranging from 46.2% to 76.8%. Fluorescence in situ hybridization (FISH) of B. tabaci China 1 in nymphs and adults revealed that OLOs are confined to the bacteriome and co-occur with “Ca. Portiera aleyrodidarum.” The vertical transmission of OLO was demonstrated by detection of OLO at the anterior pole end of the oocytes through FISH. Quantitative PCR analysis of population dynamics suggested a complex interaction between “Ca. Portiera aleyrodidarum” and OLO. Based on these results, we propose “Candidatus Hemipteriphilus asiaticus” for the classification of this symbiont from B. tabaci.